Georgie said:

2t + 8 = 5

_____

6

12t + 48 = 30

12t = 30- 48

12t = -12

t = -1

You could check this yourself, Georgie. Substitute -1 for "t" in the original equation:

[ 2(-1) + 8 ] / 6 = 5

[-2 + 8 ] / 6 = 5

6 / 6 = 5

1 = 5 <-----------NOT TRUE. So, you know your solution is incorrect.

It appears that you tried to multiply both sides of the original equation by 6 to get rid of the fraction:

6 * [(2t + 8) / 6] = 6*5

On the left side, multiplying by 6 "undoes" the division by 6, and you will be left with

2t + 8 = 30

Now, subtract 8 from both sides:

2t + 8 - 8 = 30 - 8

2t = 22

Divide both sides by 2:

(2t) / 2 = 22 / 2

t = 11

Check. Substitute 11 for t in the original equation:

[ 2(11) + 8 ] / 6 = 5

[22 + 8 ] / 6 = 5

30 / 6 = 5

5 = 5 <-------True! It checks.

I hope this helps you.